Dense nonaqueous phase liquids back diffusion controlled by biodegradation and heterogeneous sorption-desorption. (1st January 2023) - Feng, Chen; Liu, Fei; Huang, Fuyang; Chen, Linpeng; Bi, Erping
Abstract: The environmental behavior of dense non-aqueous liquids (DNAPLs) pollutants and the corresponding remediation measures have been widely studied. In recent years, many studies have shown that the back diffusion behavior of DNAPLs in the low permeability zone (LPZ) significantly affects remediation efficiency. The types and concentration levels of DNAPL contaminants are of interest in field investigations related to back diffusion in the LPZ. The temporal variation in pollutant types and concentrations in the high permeability zone (HPZ) reveals complex environmental behaviors of pollutants in the LPZ. This study focuses on the macroscopic influence of LPZ microprocesses of biodegradation and sorption-desorption on back diffusion. The effects of the biodegradation process on back diffusion are discussed by comparing microbial data and pollutant degradation characteristics in the field. According to the results of laboratory experiments and numerical simulations, the back diffusion rate was limited by the heterogeneous sorption and desorption processes of DNAPLs in the LPZ. In addition, a conceptual model of back diffusion controlled by biodegradation and sorption-desorption coupling was constructed in this review. Four novel hypotheses were proposed for further research into the microscopic influence mechanism of back diffusion to support more effective remediation measures in the future. Graphical abstract: Image 1 Highlights: The lifetime of the contamination plume is determined by back diffusion. There are other complex environmental behaviors before back diffusion. Biodegradation dominates in the low permeability zone. Back diffusion efficiency is significantly affected by heterogeneity. Conceptual models and hypotheses driven by biodegradation and sorption are proposed.